FUM2, a Cytosolic Fumarase, Is Essential for Acclimation to Low Temperature in Arabidopsis thaliana . Issue 1 (20th July 2016) - Dyson, Beth C.; Miller, Matthew A.E.; Feil, Regina; Rattray, Nicholas; Bowsher, Caroline G.; Goodacre, Royston; Lunn, John E.; Johnson, Giles N.
Abstract : Accumulation of fumaric acid, catalyzed by a cytosolic fumarase, is essential for Arabidopsis thaliana to acclimate photosynthesis to low temperature. Abstract: Although cold acclimation is a key process in plants from temperate climates, the mechanisms sensing low temperature remain obscure. Here, we show that the accumulation of the organic acid fumaric acid, mediated by the cytosolic fumarase FUM2, is essential for cold acclimation of metabolism in the cold-tolerant model species Arabidopsis ( Arabidopsis thaliana ). A nontargeted metabolomic approach, using gas chromatography-mass spectrometry, identifies fumarate as a key component of the cold response in this species. Plants of T-DNA insertion mutants, lacking FUM2, show marked differences in their response to cold, with contrasting responses both in terms of metabolite concentrations and gene expression. The fum2 plants accumulated higher concentrations of phosphorylated sugar intermediates and of starch and malate. Transcripts for proteins involved in photosynthesis were markedly down-regulated in fum2.2 but not in wild-type Columbia-0. Plants of fum2 show a complete loss of the ability to acclimate photosynthesis to low temperature. We conclude that fumarate accumulation plays an essential role in low temperature sensing in Arabidopsis, either indirectly modulating metabolic or redox signals or possibly being itself directly involved in cold sensing.